Assessment of Knowledge Regarding Life-Sustaining Treatment Plans and Attitude Towards Withdrawal of Life-Sustaining Treatment Among Staff Nurses at Tertiary Health Care Hospital - Arshad, Rabia; Rashid, Anjum (Biological and Clinical Sciences Research Journal, 2025)
Life-sustaining treatment (LST) and decisions regarding its withdrawal present significant ethical and clinical challenges in healthcare. As frontline providers, nurses play a crucial role in end-of-life care decision-making. Understanding their knowledge and attitudes towards LST is essential, especially in countries like Pakistan, where cultural and religious influences strongly impact medical practices. Objective: To assess the knowledge regarding life-sustaining treatment plans and attitudes towards withdrawing life-sustaining treatment among staff nurses working in a tertiary care hospital in Lahore, Pakistan. Methods: Using convenience sampling, a descriptive cross-sectional study was conducted among 150 registered nurses. Data were collected using a structured, adapted questionnaire comprising demographic details, knowledge-based questions, and attitude-related statements. Nurses with more than one year of experience were included. Data were analyzed using SPSS version 25, with descriptive statistics and chi-square tests applied. Results: Out of 150 participants, the majority (74.7%) were aged 31–40, and all were female. Regarding knowledge, 26.3% demonstrated high knowledge, 35.3% had average knowledge, and 38.3% had low knowledge. Most nurses (76%) believed CPR is more effective in healthy individuals, while only 30% believed that half of the seriously ill patients survive CPR. On attitudes, 57.3% had a good attitude towards ethically managing withdrawal of LST, and 100% respected religious reasons for such decisions. Conclusion: The study revealed moderate knowledge and relatively positive attitudes among nurses regarding LST and its withdrawal. Educational interventions, ethical training, and institutional guidelines are needed to enhance nurses' understanding and confidence in end-of-life care decisions.